Evolution of Islamic Education in Pakistan: Tradition, Modernization, Challenges, and Future Reforms - Sain, Zohaib Hassan; Sovia Mas Ayu; Junaidah Junaidah (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
Islam came to Pakistan in the seventh century, pioneering Islamic education systems in the region. Over the centuries, political, social, and economic developments influenced its evolution. This article explores Islamic education in Pakistan, focusing on course content, pedagogy, and infrastructure changes. The analysis begins with the earliest Islamic schools, particularly the madrasa system, which trained leaders and intellectuals in Islamic ethics, law, and theology. These institutions preserved and transmitted Islamic culture and knowledge across generations. Islamic education changed significantly during British colonial rule and industrialisation in the 19th and 20th centuries. Western principles were integrated into the madrasa curriculum, adding Mathematics, Science, and English, creating a shift from traditional methods. After independence, Pakistan expanded its Islamic education with universities and colleges. These institutions combined Islamic teachings with modern disciplines to provide a comprehensive curriculum. Today, Islamic education in Pakistan is vibrant and diverse, with institutions focusing on Islamic studies, Quranic studies, and Islamic law. While the government has implemented regulatory bodies to ensure quality, challenges like training instructors and incorporating technology persist. Collaborative efforts by religious scholars, educators, and policymakers are essential to modernising Islamic education and ensuring its relevance.